Commitment and Conflict in Multilateral Bargaining - Topi Miettinen; Christoph Vanberg (Helsinki Graduate School of Economics, 2023)
We theoretically investigate the effects of strategic pre-commitment in multilateral dynamic bargaining. Each round features a commitment stage in which players can declare that they will reject any proposal giving them less than a self-imposed threshold. Such declarations bind in the ensuing voting stage with an exogenously given probability. We characterize the set of Markov perfect equilibria under all q-majority rules. Under unanimity rule, an inefficient equilibrium always exists, and efficient equilibria exist only if the probability that commitments bind is sufficiently large and the number of players is sufficiently small. Under any (super)majority rule, every equilibrium is efficient. The results suggest that the unanimity rule is particularly damaging if the number of legislators is large and the time lags between consecutive sessions are long.
Keywords: C7; D7; 330; bargaining; commitment; conflict; delay; environmental agreements; international negotiations; legislative; majority; multilateral; unanimity